Indians of the "New Kingdom of Granada" in the 17th century city of Lima - Vega Loyola, José Javier (2022)
The presence in the city of Lima at the beginning of the seventeenth century, of "Indians of the New Kingdom of Granada" is studied, based on the information recorded in the Lima Indians Register of 1613, contrasted with information from the Archbishop's Archives of Lima and of the General Archive of the Nation. It was found that they were mostly from Muisca and Muxo tribes from the current territory of Colombia, who migrated voluntarily first to other areas of the Peruvian viceregal territory and then to the city of Lima. According to the elaborated population profile, males predominated with 80% over 20% of females; young people under 26 years of age with 66.6%, over 33.3% of 26 or more, the age limits being 16 and 50 years; and according to their marital status, singles with 73.3%, married 3% and widowed 6.6%. Regarding the economic activity carried out, 46.6% were engaged in domestic service, 26.6% in tailoring, and to a lesser extent in trades such as shoemaker, hosier, carder and muleteer. They participated in the economic and social life of the city of Lima, some even getting involved in the generalized trade of contraband merchandise brought from Asia. Regarding marriage preference, the few married people did so with Indians from Chile and Asia. It is concluded that the "Indians of the Nuevo Reyno de Granada" were free immigrants, predominantly male, young, single, engaged in domestic service and, to a lesser extent, in some craft activities.